2018
DOI: 10.1039/c8ra08512a
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on arsenic removal from water using iron-based adsorbents

Abstract: The recent developments on iron-based adsorbents such as iron oxyhydroxides nanoparticles, zero-valent iron, bimetallic oxides, and iron oxyhydroxide-doped composite materials are fully discussed in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(183 citation statements)
references
References 215 publications
(181 reference statements)
4
153
0
1
Order By: Relevance
“…This negligible amount of E a indicates the physical nature of the adsorption process. Therefore, the reaction is not temperature-sensitive, which confirmed that the system was controlled by the diffusion process [42].…”
Section: The Activation Energy Of Adsorptionmentioning
confidence: 80%
“…This negligible amount of E a indicates the physical nature of the adsorption process. Therefore, the reaction is not temperature-sensitive, which confirmed that the system was controlled by the diffusion process [42].…”
Section: The Activation Energy Of Adsorptionmentioning
confidence: 80%
“…The main processing technologies for arsenic removal include electroless deposition, membrane filtration, adsorption processes, and ion exchange [100]. There are a number of works using nanoscale materials as adsorbents of toxic arsenic compounds, such as copper oxide NPs [33,[102][103][104], composites based on nickel ferrite and polyaniline [105], copper and carbon nanotubes [36], zinc sulfide NPs in the cysteine-ZnS:TiO 2 system [106], and Fe/Cu NPs [107]; moreover, a number of review papers are available [108][109][110][111]. Thus, research aimed at preventing arsenic contamination of groundwater and/or mitigating the consequences of such contamination is very remarkable and timely.…”
Section: Flow-through Removal Of As(iii)mentioning
confidence: 99%
“…High association constants for iron with biomass are widely known. For example, biomass has been considered as a medium to immobilize iron for arsenic remediation [60]. Arantes et al [52] showed that fixed beds of milled wood could completely remove iron from dilute solutions.…”
Section: Discussionmentioning
confidence: 99%